Analyzing the Impact: The Role of MSME Growth in Reducing Unemployment Amidst High Levels of Poverty - Sunaryono, Sunaryono; Apriani, Tia; Ekobelawati, Fransiska (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
This study employs a quantitative research method to examine the impact of the number of MSMEs and poverty rates on unemployment rates in Indonesia from 2011 to 2022, utilizing data from the Central Bureau of Statistics (BPS Indonesia) and Bank Indonesia. The analysis reveals a significant relationship between the increase in MSMEs, poverty index fluctuations, and unemployment rate changes during this period. The findings demonstrate a strong correlation between the growth of MSMEs and a reduction in unemployment, whereas the relationship between poverty levels and unemployment rates is weak. This suggests that the expansion of MSMEs is an effective strategy for reducing unemployment and improving economic conditions. The study aims to enhance understanding of the factors influencing unemployment and the challenges policymakers face, providing valuable insights for efforts to combat unemployment. Additionally, the dataset used may benefit other studies addressing unemployment issues in Indonesia and similar regions. The results confirm the crucial role of MSME development in lowering unemployment rates, highlighting its potential as a viable policy approach for economic improvement.